2023
DOI: 10.1021/acs.jpca.2c07657
|View full text |Cite
|
Sign up to set email alerts
|

Do Models beyond Hybrid Density Functionals Increase the Agreement with Experiment for Predicted NMR Chemical Shifts or Electric Field Gradient Tensors in Organic Solids?

Abstract: Ab initio predictions of chemical shifts and electric field gradient (EFG) tensor components are frequently used to help interpret solid-state nuclear magnetic resonance (NMR) experiments. Typically, these predictions employ density functional theory (DFT) with generalized gradient approximation (GGA) functionals, though hybrid functionals have been shown to improve accuracy relative to experiment. Here, the performance of a dozen models beyond the GGA approximation are examined for the prediction of solid-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…The last major error source is conformational flexibility, which is considered, e.g., by the CREST (conformer–rotamer ensemble sampling tool) approach in combination with CENSO (command-line energetic sorting of conformer–rotamer ensembles) that can be used to calculate ensemble-based NMR spectra . In addition, it has been suggested that other dynamic effects are of great importance especially for solid state NMR shift predictions, where their contribution to the final value can be larger than the contribution of the electron correlation . In these cases, (path integral) molecular dynamics simulations can be used to treat the dynamic effects.…”
Section: Methodsmentioning
confidence: 99%
“…The last major error source is conformational flexibility, which is considered, e.g., by the CREST (conformer–rotamer ensemble sampling tool) approach in combination with CENSO (command-line energetic sorting of conformer–rotamer ensembles) that can be used to calculate ensemble-based NMR spectra . In addition, it has been suggested that other dynamic effects are of great importance especially for solid state NMR shift predictions, where their contribution to the final value can be larger than the contribution of the electron correlation . In these cases, (path integral) molecular dynamics simulations can be used to treat the dynamic effects.…”
Section: Methodsmentioning
confidence: 99%
“…The three components on the diagonal, by convention, are referred to as | V x x | | V y y | | V z z | A number of metrics can be used to evaluate the quality of an EFG calculation, including consideration of all three independent components of the EFG tensor. Experiments related to the EFG are only sensitive to V zz and, as has been done in other recent reports, , we will only consider V zz in our analyses and not the other, smaller elements.…”
Section: Methodsmentioning
confidence: 99%
“…The Sternheimer approximation is computationally advantageous and has been used effectively in simulations of EFG dynamics, but its usefulness is limited due to the dependence of the empirical coefficients used in relation on the specific system and its geometry. Additionally, its validity in the condensed phase has been questioned, and the addition of higher-order terms in the electronic response has been proposed. , The need for explicit quantum mechanical treatment of the electrons in the molecule is thus commonly recognized in the community; therefore, several non-embedding quantum mechanical approaches have been used by various researchers. One method models only the nearest atoms in the system and neglects the environment completely, another targets only the shift in the largest diagonal component of the EFG relative to a reference calculation, and other approaches are based on the error compensation ansatz. , In this work, we turn to the explicit quantum-mechanical treatment of the embedded species and embedding methods based on frozen-density embedding theory (FDET), in which the embedding potential (multiplicative embedding operator) is given as a sum of the classical electrostatic component and the nonclassical part representing the quantum confinement by means of a universal bifunctional. …”
Section: Introductionmentioning
confidence: 99%
“…NMR crystallography can frequently solve the experimental crystal structure even when that structure is not the most stable one predicted by the CSP. Unsurprisingly, models which predict chemical shis more accurately [263][264][265][266] enhance the discrimination between correct and incorrect structural assignments in NMR crystallography. 267 Further synergies between experiment and computation are also possible in NMR crystallography.…”
Section: Nmr Crystallographymentioning
confidence: 99%